Evaluation of trimetazidine in alleviating paclitaxel-induced peripheral neuropathy in breast cancer patients: a randomized controlled trial - Iqbal, Asmaa N.; Mady, Fatma M.; Sadek, Eman Mohamed; Abdullah, Noha M.; Abdel-Azeez, Ahmad Mostafa; Shorog, Eman; Wahsh, Engy A. (Frontiers in Pharmacology, 2026)
BackgroundPaclitaxel-induced peripheral neuropathy is a frequent chemotherapy complication that causes nerve damage and profoundly reduces patients’ quality of life. Despite extensive preclinical evidence supporting the neuroprotective potential of trimetazidine against peripheral neuropathy, its clinical efficacy remains unexplored.ObjectivesThis proof-of-concept randomized controlled trial aimed to investigate the effect of trimetazidine administered during the early phase of treatment on the incidence of paclitaxel-induced peripheral neuropathy in patients with non-metastatic breast cancer.MethodsThis parallel randomized placebo-controlled blinded endpoint trial was conducted at the Oncology Center, Minia University, Egypt, involving 60 breast cancer patients scheduled to receive weekly paclitaxel 90 mg/m2. Patients were randomized to receive either trimetazidine 35 mg once daily or placebo alongside standard care. Measurements included the incidence of paclitaxel-induced neuropathy assessed by the National Cancer Institute’s Common Terminology Criteria for Adverse Events (NCI-CTCAE) version 5.0, patient quality of life via the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group–Neurotoxicity (FACT-GOG-Ntx) subscale, and exploratory serum biomarkers, specifically nerve growth factor (NGF) levels. Neuropathy and biomarkers were evaluated over an 8-week period.Main ResultsThe incidence of grade 2 and 3 peripheral neuropathies was significantly lower in the trimetazidine group compared to controls, with notable reductions in paresthesia (p = 0.037), peripheral motor neuropathy (p = 0.004), and dysesthesia (p = 0.045), except for peripheral sensory neuropathy (p = 0.152). Clinically significant worsening in neuropathy-related quality of life was more frequent in the control group compared to the trimetazidine group (p = 0.001). Additionally, the trimetazidine group exhibited a significantly greater percentage increase in serum nerve growth factor from baseline (p = 0.003).ConclusionTrimetazidine offers a safe and effective option for mitigating early paclitaxel-induced peripheral neuropathy in breast cancer patients. Further large-scale studies with longer follow-up are warranted to confirm these findings and explore effects across different chemotherapy regimens.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06459193, identifier NCT06459193.